ALKALI EARTH ELEMENTS IN VENDIAN-CAMBRIAN CLAYEY ROCKS, THE EAST EUROPEAN PLATFORM - Felitsyn S.B. (My University, 2006)
Low Sr and Ca contents in fine-grained terrigenous rocks of the Vendian sedimentary cover in the East European Platform may be related to the following reasons: (1) the absence of authigenic carbonates in Vendian mudstones owing to desalination of epiplatformal sedimentary basins; (2) significant contribution of the chemically weathered rocks in the formation of the Vendian cover of the East European Platform. © Pleiades Publishing, Inc. 2006.
Keywords: Cambrian; Vendian; Paleozoic::Cambrian; Палеозой::Кембрийская; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский